Lower gastrointestinal polypectomy competencies in the United Kingdom: a retrospective analysis of Directly Observed Polypectomy Skills (DOPyS) - Rajendran, Arun; Thomas-Gibson, Siwan; Bassett, Paul; Dunckley, Paul; Rameshshanker, Rajaratnam; Sevdalis, Nick; Haycock, Adam (Endoscopy, 2020)
Background Polypectomy is often the most hazardous part of colonoscopy. There is significant variability in polypectomy training and assessment internationally. DOPyS (Directly Observed Polypectomy Skills) is a validated assessment tool and is used to demonstrate polypectomy competency in the UK. This study aimed to describe the learning curve for polypectomy competency in UK trainees. Methods Retrospective DOPyS data (January 2009 to September 2015) were obtained from the UK Joint Advisory Group (JAG) for intestinal endoscopy training system (JETS) national database. The number of lower gastrointestinal (LGI) procedures, overall cecal intubation rate (CIR), procedure intensity, and time in days to the first DOPyS assessment were recorded, and time to JAG certification was calculated. Results 4965 DOPyS assessments from 336 trainees were analyzed. Within the study period, 124 and 53 trainees achieved provisional and full colonoscopy certification, respectively. Trainees started formative assessment of polypectomy after > 130 LGI procedures and with a CIR of > 70 %. Within 3 years from the first DOPyS assessment, 94 % of trainees achieved provisional certification, and 50 % full certification. Higher procedure intensity at baseline DOPyS assessment was associated with a higher likelihood of obtaining certification sooner.Conclusion There is a significant variation in time to competency, and this potentially reflects the time necessary to acquire polypectomy skills. There is a need to start polypectomy training earlier, once sufficient skills, such as tip control, have been achieved to shorten the time to competency. Overall, the CIR could be used as a guide for such technical skills. Increasing exposure to training lists also potentially reduces the time to polypectomy competency.